Improving Sustainability of Steel Roofs: Life Cycle Assessment of a Case Study Roof - Krishanu Roy; Aflah Alamsah Dani; Hartej Ichhpuni; Zhiyuan Fang; James B. P. Lim (Applied Sciences, 2022)
In New Zealand (NZ), steel roofing is the most common roofing type for residential buildings. However, the environmental impact of steel roofs are not negligible. Steel roofs account for up to 30% of the upfront embodied carbon for a typical NZ house, highlighting the importance of investigating and reducing the environmental impacts of steel roofs in meeting the net-zero carbon goal of the NZ government. There are several research gaps in investigating the impacts of steel roofs, such as the variation in emissions between local and imported steel coil products, the unavailability of life cycle assessment (LCA) data, and additional impacts from ancillary items. Therefore, this study performed an LCA of a case study roof in NZ to investigate these gaps using GaBi Ts software. It was found that the overall impacts from the steel roofs, including the ancillary items, were 12 kg CO2-eq/m2, where the ancillary items accounted for less than 10% of total emissions. The prepainted steel coils manufactured globally had less than 70% emissions when compared to the emissions of locally manufactured prepainted steel coils. In addition, the roll forming processes had an insignificant effect on overall emissions, whereas the transportation of steel coils had a notable impact.